#TITLE_ALTERNATIVE# - LUTHFIAN GUMILAR (NIM 15106005); Pembimbing: Dr. rer. Nat. Wiwin Windupranata, ST., M.Si., da, HAFIDZ
Abrasion and sedimentation phenomenon frequently occured in Indonesian coastal zone. Both of them can be caused by coastal dynamics and human interface. Abrasion's and sedimentationÃ‚Â’s impact can be harm, such as land loss and potential economic decreasing in an area. One of the areas in Indonesia that have high rate of abrasion and sedimentation in coastal areas is Indramayu District. To prevent the harm impact caused by abrasion and sedimentation that occurs, the rate of abrasion and sedimentation in coastal areas of Indramayu district need to be calculated. In this research, the calculations of it's rate using Landsat imagery of Indramayu in 2001, 2003, 2005, 2007, and 2009 with six (6) different methods. The methods are rationing, density slicing, spatial filtering, composite RGB, AGSO and BILKO algorithm. The results of the rate calculations in 2001 untill 2009 show many differences in every methods. The differences occurred because every methods gives a different way to determined a land and sea border. Rationing and BILKO algorithm in processing by using Landsat imagery in 2009 gave the best results when compared to the Indramayu shoreline survey in 2010.